Usborne Phonics Readers : Ted's Shed - Phil Roxbee Cox (London, United Kingdom Usborne Publishing Ltd, 2006)
This is a story about Ted. He decides he is not content with just a red bed, he wants a red shed too. Some pages have fold-out-flaps which give young readers a chance to guess what might happen next.
Keywords: PY - Language